The Influence of the Family Environment, Utilization of Social Media Marketing, and Entrepreneurial Orientation on the Performance of Millennial SMEs in Makassar City - Roni Herison; Ifah Finatry Latiep; A. Reski Fausia Putri (Universitas Kristen Indonesia Toraja, 2022)
Business performance is something that must be considered by SMEs, including millennials. The purpose of this study is to find out the extent of the role of the environment, the use of social media marketing and entrepreneurial orientation towards the performance of Millennial SMEs in Makassar City. This research is a quantitative study using data from the distribution of questionnaires and processed using SmartPLS 4 software. The results of the study found that the family environment, the useof social media marketing and entrepreneurial initiatives can partially improve the performance of Millennial SMEs in Makassar City. Keywords: , , .